Constraint control method of optimization and its application to design of steel frames - Mansouri, S F; Maheri, M R (Scientia Iranica. Transaction A, Civil engineering, 2019)
Different optimization methods are available for optimum design of structures including classical optimization techniques and metaheuristic optimization algorithms. However, engineers do not generally use optimization techniques to design a structure. They attempt to decrease the structural weight and increase its performance and efficiency, empirically, by changing the variables and controlling the constraints. Based on this professional engineering design philosophy, in this paper, a simple algorithm, termed the Constraint Control Method (CCM), is developed and presented whereby optimum design is achieved gradually by controlling the problem constraints. Starting with oversized sections, the design was gradually improved by changing sections based on a 'control function' and controlling the constraints to be below the target values. As the constraints moved towards their targets, the design moved towards an optimum. The general functionality of the proposed algorithm was first demonstrated by solving several linear and nonlinear mathematical problems, which had exact answers. The performance of the algorithm was then evaluated through comparing design optimization results of three 2D steel frame benchmark problems with those of other metaheuristic optimization solutions. The proposed method led to the minimum structural weight while performing a considerably small number of structural analyses compared to other optimization methods.